Characteristics of drug users admitted in Lido Rehabilitation Center during 2022 - Putri, Anzany Tania Dwi; Ayuningtyas, Dumilah (Intelektual Pustaka Media Utama, 2023)
The increasing trend of illicit drug use leaves a huge concern for health and behavioral changes, including in Indonesia. Rehabilitation is a series of treatments designed to help them recover from addiction and its impacts comprehensively. The present study aimed to explore the demographic characteristic and drug use profiles of clients admitted in Lido Rehabilitation Center, the national referral center for drug use treatment in Indonesia, during 2022. A survey study was carried out quantitatively using a 2022 database of client admission in February 2023. Descriptive analysis was performed to present the data as appropriate. The overall total of drug users was 592 clients (569 males, 23 females). The demographic characteristics were dominated by young adults (79.90%), voluntary (74.70%), Muslims (86.80%), high-school-to-higher graduates (74.70%), and employers (61.80%). The drug mostly used was methamphetamines (69.80%) with duration being less than 10 years (75.50%) and addiction level being mild-to-moderate (92.80%). The main reasons for starting drug use were peer/partner pressure (37.18%) and curiosity (29.92%). From this study, we can see that the trend of methamphetamine use in productive ages is still dominating in 2022. Further study is needed to evaluate the outcomes of the treatment they have received during the rehabilitation program.